2013
DOI: 10.1371/journal.pone.0082650
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Androgen Receptor Expression on Breast Cancer Survival: A Retrospective Study and Meta-Analysis

Abstract: Recent studies have highlighted the role of androgen receptor (AR) as a prognostic biomarker of breast cancer. However, its predictive role in disease free survival (DFS) and overall survival (OS) still remains inconclusive. The present study aimed to retrospectively investigate the association between AR and survival outcomes in breast cancer and also identify this association by a meta-analysis of published researches. Clinical data from 109 patients with breast cancer, who underwent surgery at Ruijin Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
5
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 25 publications
(14 reference statements)
13
70
5
6
Order By: Relevance
“…In contrast, a recent meta-analysis found that increased AR expression predicted good outcome in this subset of breast cancer patients (Qu et al 2013). Another confounding factor is the fact that basal and TN breast cancer are not synonymous, and standardised criteria for defining both subgroups have not been defined.…”
Section: :4mentioning
confidence: 94%
“…In contrast, a recent meta-analysis found that increased AR expression predicted good outcome in this subset of breast cancer patients (Qu et al 2013). Another confounding factor is the fact that basal and TN breast cancer are not synonymous, and standardised criteria for defining both subgroups have not been defined.…”
Section: :4mentioning
confidence: 94%
“…subtypes expressing AR and improved OS in ER-positive BCs expressing AR (Qu et al 2013). Conversely, some studies did not report a better outcome (Park et al 2011) or observed an even poorer prognosis (Choi et al 2015) in AR-positive/ER-negative BC.…”
Section: :10mentioning
confidence: 97%
“…Discrepancies in study results could be explained by multiple factors, including the following: i) the use of tissue microarrays vs whole-tissue sections; ii) use of different AR protein detection techniques (radioligand binding, immunohistochemistry (IHC) or reverse-phase protein array); iii) use of different antibodies for AR immunodetection; iv) measurement of AR mRNA via different platforms in transcriptome profiling studies; v) use of different cut-off scores to define AR positivity and vi) differences in clinical parameters such as sample size, prior treatment regimens, length of follow-up and tumour type. Two recent meta-analyses have reported that AR expression is associated with better breast cancer outcomes (Qu et al 2013, Vera-Badillo et al 2014. However, numerous shortcomings associated with these analyses, most notably the exclusion of several key studies, limit their use in further clarifying the prognostic value of AR.…”
Section: Prognostic Value Of Ar Expression In Breast Cancermentioning
confidence: 99%